SISTEM INFORMASI PENJUALAN TERINTEGRASI ANDROID: SOLUSI DIGITALISASI UMKM DALAM ERA EKONOMI DIGITAL (STUDI KASUS: KUGAR MINAMAS PANSELA) - Manurung, Ria; Sipahutar, Tetty Tiurma; Nainggolan, Benny Rojeston Marnaek (LPPM Poltek ST Paul, 2024)
This study shows how an Android-integrated sales information system can help MSMEs face challenges in the digital economy era and take advantage of growth opportunities. It also aims to improve sales efficiency in providing services to customers by designing a digitalization-based sales system with an Android model. Data collection, analysis, design, development, and testing comprise prototype method of system development. Based on the Paired Samples Test results, it is clear that H0 is rejected and H1 is accepted because the Sig value is 0.00, which means that the Sig value is less than 0.05. Based on hypothesis testing, therefore, the Sig value is less than 0.05. As demonstrated by a case study on Kugar Minamas Pansela, one of the solutions for the digitalization of MSMEs in a digital economy is the implementation of an integrated sales information system. The results of system testing show that average time before using the system is 7.42 minutes and the average time after using the system is 3.81 minutes. The results indicate that this system could be used to speed up Salt's sales and payment process with Android integration and become one of the solutions for the digitalization of MSMEs in the digital era.